2020
DOI: 10.1051/e3sconf/202017515028
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture faculty students’ meanings translation in conditions of the development of communicative competence

Abstract: This article discusses psychological characteristics of communicative and speech competence of the agriculture faculty students. The authors pay attention to the study of students communication skills in the process of interaction, their ability to translate meaning, skills of information interpretation and effective meaning transfer. The study involved 120 students aged 17 to 23 years (M=20.75, SD=2.25 (37% men). Methods were used: a survey – “Communicative competence” of L. Michelson in the modification of Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The fears of adult respondents of the "Transition" generation are associated in our study with the loss of meaning in some aspects of life, the loss of feelings, and the destruction of relationships with others [36,37]. This is combined with a study by Volková, Dušková (2015), which showed that for adults, partner-related fears and employment-related fears can be typical.…”
Section: Discussionsupporting
confidence: 57%
“…The fears of adult respondents of the "Transition" generation are associated in our study with the loss of meaning in some aspects of life, the loss of feelings, and the destruction of relationships with others [36,37]. This is combined with a study by Volková, Dušková (2015), which showed that for adults, partner-related fears and employment-related fears can be typical.…”
Section: Discussionsupporting
confidence: 57%
“…Generations X and Y were formed in the information age [15], so they have many similar mental formations [16,23,24]. Hence, behavior models can be transferred not only by the 210, 20007 (2020) E3S Web of Conferences ITSE-2020 https://doi.org/10.1051/e3sconf/202021020007 family, but for example, by mass media that can offer a repertoire of life scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Features of the formation of the ability to transfer meanings in students of different courses in the educational process are considered in the works of Suroedova E., Tushnova Yu. and Belousova E. And it was found that students of the third year have the highest indicators of communicative competence and verbal activity [22]. In the works of Nikolenko O., Zheldochenko L. and Lomova N. [23], the role of semantic organization of the educational process in the formation of students ' values is shown.…”
Section: Introductionmentioning
confidence: 96%